Is a simplified Finite Element model of the gluteus region able to capture the mechanical response of the internal soft tissues under compression?. (January 2020) - Macron, Aurélien; Pillet, Hélène; Doridam, Jennifer; Rivals, Isabelle; Sadeghinia, Mohammad Javad; Verney, Alexandre; Rohan, Pierre-Yves
Abstract: Background: Internal soft tissue strains have been shown to be one of the main factors responsible for the onset of Pressure Ulcers and to be representative of its risk of development. However, the estimation of this parameter using Finite Element (FE) analysis in clinical setups is currently hindered by costly acquisition, reconstruction and computation times. Ultrasound (US) imaging is a promising candidate for the clinical assessment of both morphological and material parameters. Method: The aim of this study was to investigate the ability of a local FE model of the region beneath the ischium with a limited number of parameters to capture the internal response of the gluteus region predicted by a complete 3D FE model. 26 local FE models were developed, and their predictions were compared to those of the patient-specific reference FE models in sitting position. Findings: A high correlation was observed (R = 0.90, p-value < 0.01). A sensitivity analysis showed that the most influent parameters were the mechanical behaviour of the muscle tissues, the ischium morphology and the external mechanical loading. Interpretation: Given the progress of US for capturing both morphological and material parameters, these results are promising because they open up the possibility to use personalised simplified FE models for risk estimation in daily clinical routine. Highlights: Internal strain has been shown to be one of the main factors responsible for the onset of PU. Estimation thereof using 3D patient-specific computer models in clinical setups is challenging. Results show that a local model can capture the internal response of the gluteus region predicted by a complete 3D FE model Mechanical behavior of muscle, ischium morphology and external mechanical loading constitute the most influent parameters Given the progress of US for capturing both morphological and material parameters, these results are promising